2014
DOI: 10.14245/kjs.2014.11.2.39
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Laminoplasty in the Elderly Patients with Cervical Spondylotic Myelopathy

Abstract: ObjectiveThe purpose of this study is to evaluate clinical and radiological outcomes analysis of the laminoplasty in the elderly patients, and to compare with the non-elderly patients.MethodsA retrospective study of the short term result in patients who had treated with the laminoplasty for cervical spondylotic myelopathy (CSM) was performed. From January 2008 to December 2012, total 62 patients were operated with single open-door technique because of CSM; 28 patients were the elderly and 34 patients were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…(4, [11][12][13]19,22,25) Blood loss has been reported at 250-380ml in cases of laminectomy applied for CSM. In a study by Bydon et al (2), pediatric cases of achondroplasia operated on with UBS and HSD were compared and dura injury was reported in 9 (45%) cases where HSD had been used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4, [11][12][13]19,22,25) Blood loss has been reported at 250-380ml in cases of laminectomy applied for CSM. In a study by Bydon et al (2), pediatric cases of achondroplasia operated on with UBS and HSD were compared and dura injury was reported in 9 (45%) cases where HSD had been used.…”
Section: Discussionmentioning
confidence: 99%
“…Laminectomy surgery can be applied with different techniques and different instruments (14,19). Classic cervical laminectomy is performed with a Kerrison rongeur.…”
mentioning
confidence: 99%
“…In this paper [40], they explained that this was due to the non-CSM diseases including lumbar spine canal stenosis, osteoarthritis of knee, carpal tunnel syndrome, and stress urine incontinence. Moreover, Son et al [41] reported that laminoplasty resulted in good clinical outcomes in the elderly (65 years old), which were the same as in the non-elderly subjects. Similarly, Heller et al [42] reported that both laminoplasty approaches exhibited similar good clinical outcomes.…”
Section: Clinical Outcomementioning
confidence: 83%
“…Similarly, Heller et al [42] reported that both laminoplasty approaches exhibited similar good clinical outcomes. Furthermore, the recovery rate (RR) of laminoplasty was greater than 50% in the short-term, mid-term, and long-term follow-up [35,[38][39][40][41]. On the other hand, Uehara et al [34] reported that RR was 47.1% in the final follow-up, but 55.9% immediately after operation.…”
Section: Clinical Outcomementioning
confidence: 99%
See 1 more Smart Citation